From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Numerical study of light backscattering from layers of absorbing irregular particles larger than the wavelength - Alhaddad, Samer; Förstner, Jens; Grynko, Yevgen (Journal of Quantitative Spectroscopy and Radiative Transfer)
Keywords: tet_topic_scattering

Tailoring the directive nature of optical waveguide antennas - Farheen, Henna; Yan, Lok-Yee; Leuteritz, Till; Qiao, Siqi; Spreyer, Florian; Schlickriede, Christian; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Zentgraf, Thomas; Linden, Stefan; Myroshnychenko, Viktor; et al. (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate the numerical and experimental realization of optimized optical traveling-wave antennas made of low-loss dielectric materials. These antennas exhibit highly directive radiation patterns and our studies reveal that this nature comes from two dominant guided TE modes excited in the waveguide-like director of the antenna, in addition to the leaky modes. The optimized antennas possess a broadband nature and have a nearunity radiation efficiency at an operational wavelength of 780 nm. Compared to the previously studied plasmonic antennas for photon emission, our all-dielectric approach demonstrates a new class of highly directional, low-loss, and broadband optical antennas.
Keywords: tet_topic_opticalantenna

Optimized silicon antennas for optical phased arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate a large-scale two dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing desired radiation patterns in the far-field. The OPAs are numerically optimized to have an upward efficiency of up to 90%, targeting radiation concentration mainly in the field of view. We envision that our OPAs have the ability of generating complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation and augmented-reality displays.
Keywords: tet_topic_opticalantenna

How to suppress radiative losses in high-contrast integrated Bragg gratings - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Journal of the Optical Society of America B)
High-contrast slab waveguide Bragg gratings with 1D periodicity are investigated. For specific oblique excitation by semi-guided waves at sufficiently high angles of incidence, the idealized structures do not exhibit any radiative losses, such that reflectance and transmittance for the single port mode add strictly up to one. We consider a series of symmetric, fully and partly etched finite gratings, for parameters found in integrated silicon photonics. These can act as spectral filters with a reasonably flattop response. Apodization can lead to more box shaped reflectance and transmittance spectra. Together with a narrowband Fabry–Perot filter, these configurations are characterized by reflection bands, or transmittance peaks, with widths that span three orders of magnitude.
Keywords: tet_topic_waveguide

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

Efficient Modeling and Tailoring of Nonlinear Wavefronts in Dielectric Metasurfaces - Hähnel, David; Förstner, Jens; Myroshnychenko, Viktor (ACS Photonics)
Dielectric metasurfaces provide a unique platform for efficient harmonic generation and optical wavefront manipulation at the nanoscale. Tailoring phase and amplitude of a nonlinearly generated wave with a high emission efficiency using resonance-based metasurfaces is a challenging task that often requires state-of-the-art numerical methods. Here, we propose a simple yet effective approach combining a sampling method with a Monte Carlo approach to design the third-harmonic wavefront generated by all-dielectric metasurfaces composed of elliptical silicon nanodisks. Using this approach, we theoretically demonstrate the full nonlinear 2π phase control with a uniform and highest possible amplitude in the considered parameter space, allowing us to design metasurfaces operating as third harmonic beam deflectors capable of steering light into a desired direction with high emission efficiency. The TH beam deflection with a record calculated average conversion efficiency of 1.2 × 10–1 W–2 is achieved. We anticipate that the proposed approach will be widely applied as alternative to commonly used optimization algorithms with higher complexity and implementation effort for the design of metasurfaces with other holographic functionalities.
Keywords: tet_topic_meta

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Optimization of optical waveguide antennas for directive emission of light - Farheen, Henna; Leuteritz, Till; Linden, Stefan; Myroshnychenko, Viktor; Förstner, Jens (Journal of the Optical Society of America B)
Optical traveling wave antennas offer unique opportunities to control and selectively guide light into a specific direction, which renders them excellent candidates for optical communication and sensing. These applications require state-of-the-art engineering to reach optimized functionalities such as high directivity and radiation efficiency, low sidelobe levels, broadband and tunable capabilities, and compact design. In this work, we report on the numerical optimization of the directivity of optical traveling wave antennas made from low-loss dielectric materials using full-wave numerical simulations in conjunction with the particle swarm optimization algorithm. The antennas are composed of a reflector and a director deposited on a glass substrate, and an emitter placed in the feed gap between them serves as an internal source of excitation. In particular, we analyze antennas with rectangular- and horn-shaped directors made of either hafnium dioxide or silicon. The optimized antennas produce highly directional emissions due to the presence of two dominant guided TE modes in the director in addition to leaky modes. These guided modes dominate the far-field emission pattern and govern the direction of the main lobe emission, which predominately originates from the end facet of the director. Our work also provides a comprehensive analysis of the modes, radiation patterns, parametric influences, and bandwidths of the antennas, which highlights their robust nature.
Keywords: tet_topic_opticalantenna

Numerical analysis of the coherent mechanism producing negative polarization at backscattering from systems of absorbing particles - Alhaddad, Samer; Grynko, Yevgen; Farheen, Henna; Förstner, Jens (Optics Letters)
We study a double-scattering coherent mechanism of negative polarization (NP) near opposition that is observed for powder-like surfaces. The problem is solved numerically for absorbing structures with irregular constituents, cubes, spheres, and ellipsoids larger than the wavelength of incident light. Our simulations show that double scattering between two random irregular particles shows weak NP. Adding one more particle significantly increases the relative contribution of double scattering which enhances NP. Simulations with regular shapes and controlled geometric parameters show that the interference mechanism is sensitive to the geometry of the scattering system and can also result in no polarization or even strong enhancement of positive polarization at backscattering.
Keywords: tet_topic_scattering

Resonant evanescent excitation of OAM modes in a high-contrast circular step-index fiber - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Complex Light and Optical Forces XVI)
Resonant evanescent coupling can be utilized to selectively excite orbital angular momentum (OAM) modes of high angular order supported by a thin circular dielectric rod. Our 2.5-D hybrid-analytical coupled mode model combines the vectorial fields associated with the fundamental TE- and TM-modes of a standard silicon photonics slab waveguide, propagating at oblique angles with respect to the rod axis, and the hybrid modes supported by the rod. One observes an efficient resonant interaction in cases where the common axial wavenumber of the waves in the slab matches the propagation constant of one or more modes of the rod. For certain modes of high angular order, the incident wave is able to transfer its directionality to the field in the fiber, exciting effectively only one of a pair of degenerate OAM modes
Keywords: tet_topic_waveguide

Semi-guided waves in integrated optical waveguide structures - Ebers, Lena
In dieser Arbeit wird die elektromagnetische Wellenausbreitung in integrierten optischen Wellenleitern mit Hilfe von halb analytischen und numerischen Simulationsmethoden untersucht. Im ersten Teil werden 2-D Si/SiO2-Wellenleiterkonfigurationen mit hohem Brechungsindexkontrast betrachtet. Die Strukturen werden mit halb geführten Wellen unter schrägen Ausbreitungswinkeln angeregt. Dadurch kann die Leistungsübertragung zu bestimmten ausgehenden Moden unterdrückt werden, wodurch vollständig verlustfreie Systeme entstehen. Zusätzlich dient die Anregung mit einem seitlich begrenzten, einfallenden Wellenbündel aus halb geführten Wellen dazu, praktisch relevantere 3-D Konfigurationen zu realisieren. Darüber hinaus wird eine schrittweise Winkelspektrum-Methode vorgestellt, die es ermöglicht, in Kombination mit voll vektoriellen 2-D Finite-Elemente-Lösungen für Teilprobleme mit geringerer Komplexität, die Wellenausbreitung in planaren, linsenförmigen Wellenleitern numerisch in drei Raumrichtungen zu berechnen. Im zweiten Teil dieser Arbeit wird die Ausbreitung in Wellenleiterstrukturen aus Lithiumniobat untersucht, welche für quantenoptische Effekte genutzt werden. Zur Detektion einzelner Photonen werden supraleitende Nanodrähte auf eindiffundierten Lithiumniobat Wellenleitern mit zusätzlicher Taperschicht aus Silizium betrachtet. Um die Wellenausbreitung in diesen 3-D Wellenleitern zu beschreiben, wird eine einseitig gerichtete Finite-Elemente „Modal Matching“ Methode eingeführt. Abschließend werden Rippenwellenleiter aus Lithiumniobat analysiert, die auf Siliziumdioxid Plattformen aufgebracht sind. Der Schwerpunkt liegt hier auf dem nichtlinearen „Parametric Down-Conversion“ Prozess, der für die Erzeugung verschränkter Photonen verwendet wird.
Keywords: tet_topic_waveguide

Light backscattering from numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens
Keywords: tet_topic_scattering

Broadband optical Ta2O5 antennas for directional emission of light - Farheen, Henna; Yan, Lok-Yee; Quiring, Viktor; Eigner, Christof; Zentgraf, Thomas; Linden, Stefan; Förstner, Jens; Myroshnychenko, Viktor (Optics Express)
Highly directive antennas with the ability of shaping radiation patterns in desired directions are essential for efficient on-chip optical communication with reduced cross talk. In this paper, we design and optimize three distinct broadband traveling-wave tantalum pentoxide antennas exhibiting highly directional characteristics. Our antennas contain a director and reflector deposited on a glass substrate, which are excited by a dipole emitter placed in the feed gap between the two elements. Full-wave simulations in conjunction with global optimization provide structures with an enhanced linear directivity as high as 119 radiating in the substrate. The high directivity is a result of the interplay between two dominant TE modes and the leaky modes present in the antenna director. Furthermore, these low-loss dielectric antennas exhibit a near-unity radiation efficiency at the operational wavelength of 780 nm and maintain a broad bandwidth. Our numerical results are in good agreement with experimental measurements from the optimized antennas fabricated using a two-step electron-beam lithography, revealing the highly directive nature of our structures. We envision that our antenna designs can be conveniently adapted to other dielectric materials and prove instrumental for inter-chip optical communications and other on-chip applications.
Keywords: tet_topic_opticalantenna

Negative polarization of light at backscattering from a numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Icarus)
We model negative polarization, which is observed for planetary regoliths at backscattering, solving a full wave problem of light scattering with a numerically exact Discontinuous Galerkin Time Domain (DGTD) method. Pieces of layers with the bulk packing density of particles close to 0.5 are used. The model particles are highly absorbing and have irregular shapes and sizes larger than the wavelength of light. This represents a realistic analog of low-albedo planetary regoliths. Our simulations confirm coherent backscattering mechanism of the origin of negative polarization. We show that angular profiles of polarization are stabilized if the number of particles in a layer piece becomes larger than ten. This allows application of our approach to the negative polarization modeling for planetary regoliths.
Keywords: tet_topic_scattering

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Light Scattering by Large Densely Packed Clusters of Particles - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Springer Series in Light Scattering - Volume 8: Light Polarization and Multiple Scattering in Turbid Media)
We review our results of numerical simulations of light scattering from different systems of densely packed irregular particles. We consider spherical clusters, thick layers and monolayers with realistic topologies and dimensions much larger than the wavelength of light. The maximum bulk packing density of clusters is 0.5. A numerically exact solution of the electromagnetic problem is obtained using the Discontinuous Galerkin Time Domain method and with application of high- performance computing. We show that high packing density causes light localization in such structures which makes an impact on the opposition phenomena: backscattering intensity surge and negative linear polarization feature. Diffuse multiple scattering is significantly reduced in the case of non-absorbing particles and near-field interaction results in a percolation-like light transport determined by the topology of the medium. With this the negative polarization feature caused by single scattering gets enhanced if compared to lower density samples. We also confirm coherent double scattering mechanism of negative polarization for light scattered from dense absorbing slabs. In this case convergent result for the scattering angle polarization dependency at backscattering can be obtained for a layer of just a few tens of particles if they are larger than the wavelength.
Keywords: tet_topic_scattering

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Small-scale online simulations in guided-wave photonics - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XXVI)
Online solvers for a series of standard 1-D or 2-D problems in integrated optics will be discussed. Implemented on the basis of HTML/JavaScript/SVG with core routines compiled from well tested C++-sources, the quasi-analytical algorithms require a computational load that can be handled easily even by current mobile devices. So far the series covers the 1-D guided modes of dielectric multilayer slab waveguides and the oblique plane wave reflection from these, the modes of rectangular channel waveguides (in an approximation of effective indices), bend modes of curved multilayer slabs, whispering-gallery resonances (“Quasi-Normal-Modes”) supported by circular dielectric cavities, the hybrid modes of circular multi-step-index optical fibers, bound and leaky modes of 1-D complex multilayers, including plasmonic surface modes, and, with restrictions, quite general rectangular scattering problems in 2-D.
Keywords: tet_topic_waveguide

Far-field Calculation from magnetic Huygens Box Data using the Boundary Element Method - Marschalt, Christoph; Schroder, Dominik; Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Sievers, Denis; Förstner, Jens (2022 Smart Systems Integration (SSI))
In this publication a novel method for far-field prediction from magnetic Huygens box data based on the boundary element method (BEM) is presented. Two examples are considered for the validation of this method. The first example represents an electric dipole so that the obtained calculations can be compared to an analytical solution. As a second example, a printed circuit board is considered and the calculated far-field is compared to a fullwave simulation. In both cases, the calculations for different field integral equations are under comparison, and the results indicate that the presented method performs very well with a combined field integral equation, for the specified problem, when only magnetic Huygens box data is given.
Keywords: Near-Field Scanning; Huygens Box; Boundary Element Method; Method of Moments; tet_topic_hf

Dielectric travelling wave antennas for directional light emission - Leuteritz, T.; Farheen, H.; Qiao, S.; Spreyer, F.; Schlickriede, Christian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Linden, S. (Optics Express)
We present a combined experimental and numerical study of the far-field emission properties of optical travelling wave antennas made from low-loss dielectric materials. The antennas considered here are composed of two simple building blocks, a director and a reflector, deposited on a glass substrate. Colloidal quantum dots placed in the feed gap between the two elements serve as internal light source. The emission profile of the antenna is mainly formed by the director while the reflector suppresses backward emission. Systematic studies of the director dimensions as well as variation of antenna material show that the effective refractive index of the director primarily governs the far-field emission pattern. Below cut off, i.e., if the director’s effective refractive index is smaller than the refractive index of the substrate, the main lobe results from leaky wave emission along the director. In contrast, if the director supports a guided mode, the emission predominately originates from the end facet of the director.
Keywords: tet_topic_opticalantenna

Resonant evanescent excitation of guided waves with high-order optical angular momentum - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Journal of the Optical Society of America B)
Gaussian-beam-like bundles of semi-guided waves propagating in a dielectric slab can excite modes with high-order optical angular momentum supported by a circular fiber. We consider a multimode step-index fiber with a high-index coating, where the waves in the slab are evanescently coupled to the modes of the fiber. Conditions for effective resonant interaction are identified. Based on a hybrid analytical–numerical coupled mode model, our simulations predict that substantial fractions of the input power can be focused into waves with specific orbital angular momentum, of excellent purity, with a clear distinction between degenerate modes with opposite vorticity.
Keywords: tet_topic_waveguides

Configurable lossless broadband beam splitters for semi-guided waves in integrated silicon photonics - Hammer, Manfred; Ebers, Lena; Förstner, Jens (OSA Continuum)
We show that narrow trenches in a high-contrast silicon-photonics slab can act as lossless power dividers for semi-guided waves. Reflectance and transmittance can be easily configured by selecting the trench width. At sufficiently high angles of incidence, the devices are lossless, apart from material attenuation and scattering due to surface roughness. We numerically simulate a series of devices within the full 0-to-1-range of splitting ratios, for semi-guided plane wave incidence as well as for excitation by focused Gaussian wave bundles. Straightforward cascading of the trenches leads to concepts for 1×M-power dividers and a polarization beam splitter.
Keywords: tet_topic_waveguide

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

HighPerMeshes – A Domain-Specific Language for Numerical Algorithms on Unstructured Grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz-Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Euro-Par 2020: Parallel Processing Workshops)
Solving partial differential equations on unstructured grids is a cornerstone of engineering and scientific computing. Nowadays, heterogeneous parallel platforms with CPUs, GPUs, and FPGAs enable energy-efficient and computationally demanding simulations. We developed the HighPerMeshes C++-embedded Domain-Specific Language (DSL) for bridging the abstraction gap between the mathematical and algorithmic formulation of mesh-based algorithms for PDE problems on the one hand and an increasing number of heterogeneous platforms with their different parallel programming and runtime models on the other hand. Thus, the HighPerMeshes DSL aims at higher productivity in the code development process for multiple target platforms. We introduce the concepts as well as the basic structure of the HighPerMeshes DSL, and demonstrate its usage with three examples, a Poisson and monodomain problem, respectively, solved by the continuous finite element method, and the discontinuous Galerkin method for Maxwell’s equation. The mapping of the abstract algorithmic description onto parallel hardware, including distributed memory compute clusters, is presented. Finally, the achievable performance and scalability are demonstrated for a typical example problem on a multi-core CPU cluster.
Keywords: tet_topic_hpc

The HighPerMeshes framework for numerical algorithms on unstructured grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz‐Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Concurrency and Computation: Practice and Experience)
Keywords: tet_topic_hpc

Hybrid coupled mode modelling of the evanescent excitation of a dielectric tube by semi-guided waves at oblique angles - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optical and Quantum Electronics)
A dielectric step-index optical fiber with tube-like profile is considered, being positioned with a small gap on top of a dielectric slab waveguide. We propose a 2.5-D hybrid analytical/numerical coupled mode model for the evanescent excitation of the tube through semi-guided waves propagating in the slab at oblique angles. The model combines the directional polarized modes supported by the slab with analytic solutions for the TE-, TM-, and orbital-angular-momentum (OAM) modes of the tube-shaped fiber. Implementational details of the scheme are discussed, complemented by finite-element simulations for verification purposes. Our results include configurations with resonant in-fiber excitation of OAM modes with large orbital angular momentum and strong field enhancement.
Keywords: tet_topic_waveguides

Nonlinear dielectric properties of random paraelectric-dielectric composites - Myroshnychenko, Viktor; Smirnov, Stanislav; Jose, Pious Mathews Mulavarickal; Brosseau, Christian; Förstner, Jens (Acta Materialia)
The challenge of designing new tunable nonlinear dielectric materials with tailored properties has attracted an increasing amount of interest recently. Herein, we study the effective nonlinear dielectric response of a stochastic paraelectric-dielectric composite consisting of equilibrium distributions of circular and partially penetrable disks (or parallel, infinitely long, identical, partially penetrable, circular cylinders) of a dielectric phase randomly dispersed in a continuous matrix of a paraelectric phase. The random microstructures were generated using the Metropolis Monte Carlo algorithm. The evaluation of the effective permittivity and tunability were carried out by employing either a Landau thermodynamic model or its Johnson’s approximation to describe the field-dependent permittivity of the paraelectric phase and solving continuum-electrostatics equations using finite element calculations. We reveal that the percolation threshold in this composite governs the critical behavior of the effective permittivity and tunability. For microstructures below the percolation threshold, our simulations demonstrate a strong nonlinear behaviour of the field-dependent effective permittivity and very high tunability that increases as a function of dielectric phase concentration. Above the percolation threshold, the effective permittivity shows the tendency to linearization and the tunability dramatically drops down. The highly reduced permittivity and extraordinarily high tunability are obtained for the composites with dielectric impenetrable disks at high concentrations, in which the triggering of the percolation transition is avoided. The reported results cast light on distinct nonlinear behaviour of 2D and 3D stochastic composites and can guide the design of novel composites with the controlled morphology and tailored permittivity and tunability.

Light backscattering from large clusters of densely packed irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
We numerically simulate multiple light scattering in discrete disordered media represented by large clusters of irregular non-absorbing particles. The packing density of clusters is 0.5. With such conditions diffuse scattering is significantly reduced and light transport follows propagation channels that are determined by the particle size and topology of the medium. This kind of localization produces coherent backscattering intensity surge and enhanced negative polarization branch if compared to lower density samples.
Keywords: tet_topic_scattering

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

Towards Semiconductor-Superconductor-Crystal Hybrid Integration for Quantum Photonics - Protte, Maximilian; Ebers, Lena; Hammer, Manfred; Höpker, Jan Philipp; Albert, Maximilian; Quiring, Viktor; Meier, Cedrik; Förstner, Jens; Silberhorn, Christine; Bartley, Tim (OSA Quantum 2.0 Conference)
We fabricate silicon tapers to increase the mode overlap of superconducting detectors on Ti:LiNbO3 waveguides. Mode images show a reduction in mode size from 6 µm to 2 µm FWHM, agreeing with beam propagation simulations.
Keywords: tet_topic_waveguide

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Ultrafast electric control of a single QD exciton - Förstner, Jens; Widhalm, A.; Mukherjee, A.; Krehs, S.; Jonas, B.; Spychala, K.; Förstner, Jens; Thiede, Andreas; Reuter, Dirk; Zrenner, Artur (11th International Conference on Quantum Dots)

Method of superposing a multiple driven magnetic field to minimize stray fields around the receiver for inductive wireless power transmission - Lange, Sven; Büker, Maik-Julian; Sievers, Denis; Hedayat, Christian; Förstner, Jens; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)
This paper presents a new methodology by using a multiple coil array for energy transmission. The complex current strengths of the transmitting coil array are calculated by having the knowledge about of the mutual inductances and the symmetries of the transmitting coil array, so that its resulting magnetic field mainly penetrates only the receiving coil and is strongly attenuated outside. This method is used for an optimized wireless energy transmission but can also be implemented for other inductive applications.

Light scattering by 3-Foci convex and concave particles in the geometrical optics approximation - Stankevich, Dmitriy; Hradyska, Larissa; Shkuratov, Yuriy; Grynko, Yevgen; Videen, Gorden; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
We consider light scattering from a new type of model particle whose shape is represented in the form of a generalized ellipsoid having N foci, where N is greater than two. Such particles can be convex as well as concave. We use the geometrical optics approximation to study the light scattering from 3-foci particles. Non-zero elements of the scattering matrix are calculated for ensembles of randomly oriented independent transparent particles, m = n + i0. Several internal reflection orders are considered separately. It was found that the transmission-transmission (TT) and transmission-reflectance-transmission (TRT) components dominate in the formation of intensity of scattered light at large and small phase angles, respectively. We found a significant role of the total internal reflections of the TRT in the middle portion of the phase angle range. The main factors in the formation of positive linear polarization are the R and TRT component. The TT component is responsible for the formation of negative polarization branch at large phase angles.
Keywords: tet_topic_scattering

Oblique quasi-lossless excitation of a thin silicon slab waveguide: a guided-wave variant of an anti-reflection coating - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Journal of the Optical Society of America B)
Keywords: tet_topic_waveguides

Coupled microstrip-cavities under oblique incidence of semi-guided waves: a lossless integrated optical add-drop filter - Ebers, Lena; Hammer, Manfred; Berkemeier, Manuel B.; Menzel, Alexander; Förstner, Jens (OSA Continuum)
We investigate optical microresonators consisting of either one or two coupled rectangular strips between upper and lower slab waveguides. The cavities are evanescently excited under oblique angles by thin-film guided, in-plane unguided waves supported by one of the slab waveguides. Beyond a specific incidence angle, losses are fully suppressed. The interaction between the guided mode of the cavity-strip and the incoming slab modes leads to resonant behavior for specific incidence angles and gaps. For a single cavity, at resonance, the input power is equally split among each of the four output ports, while for two cavities an add-drop filter can be realized that, at resonance, routes the incoming power completely to the forward drop waveguide via the cavity. For both applications, the strength of the interaction is controlled by the gaps between cavities and waveguides.
Keywords: tet_topic_waveguides

Optical transition between two optical waveguides layer and method for transmitting light - Hammer, Manfred; Förstner, Jens; Ebers, Lena
Die Erfindung betrifft einen optischen Übergang zwischen zwei optischen Schichtwellenleitern. Dazu ist eine Anordnung vorgesehen aus einem ersten optischen Schichtwellenleiter (2) und einem zweiten optischen Schichtwellenleiter (3), wobei der erste optische Schichtwellenleiter (2) und der zweite optische Schichtwellenleiter (3) voneinander verschiedene über ihre jeweilige Länge konstante Dicken (d, r) aufweisen, der erste optische Schichtwellenleiter (2) mit dem zweiten optischen Schichtwellenleiter (3) mittels einer optischen Schichtwellenleiterstruktur (4) verbunden ist, die über ihre gesamte Länge (w) eine Dicke (h) aufweist, die zwischen der Dicke (d) des ersten optischen Schichtwellenleiters (2) und der Dicke (r) des zweiten optischen Schichtwellenleiters (3) liegt. Erfindungsgemäß ist die Dicke (h) der optischen Schichtwellenleiterstruktur (4) über die gesamte Länge (w) der optischen Schichtwellenleiterstruktur (4) konstant. Damit wird eine Möglichkeit für einen effizienten und mit geringen Verlusten behafteten Übergang zwischen zwei optischen Schichtwellenleitern mit unterschiedlicher Dicke bereitgestellt.
Keywords: tet_topic_waveguides

Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Solving Maxwell's Equations with Modern C++ and SYCL: A Case Study - Afzal, Ayesha; Schmitt, Christian; Alhaddad, Samer; Grynko, Yevgen; Teich, Jürgen; Förstner, Jens; Hannig, Frank (Proceedings of the 29th Annual IEEE International Conference on Application-specific Systems, Architectures and Processors (ASAP))
In scientific computing, unstructured meshes are a crucial foundation for the simulation of real-world physical phenomena. Compared to regular grids, they allow resembling the computational domain with a much higher accuracy, which in turn leads to more efficient computations. There exists a wealth of supporting libraries and frameworks that aid programmers with the implementation of applications working on such grids, each built on top of existing parallelization technologies. However, many approaches require the programmer to introduce a different programming paradigm into their application or provide different variants of the code. SYCL is a new programming standard providing a remedy to this dilemma by building on standard C ++17 with its so-called single-source approach: Programmers write standard C ++ code and expose parallelism using C++17 keywords. The application is then transformed into a concrete implementation by the SYCL implementation. By encapsulating the OpenCL ecosystem, different SYCL implementations enable not only the programming of CPUs but also of heterogeneous platforms such as GPUs or other devices. For the first time, this paper showcases a SYCL- based solver for the nodal Discontinuous Galerkin method for Maxwell’s equations on unstructured meshes. We compare our solution to a previous C-based implementation with respect to programmability and performance on heterogeneous platforms.<br
Keywords: tet_topic_hpc

Oblique incidence of semi-guided planar waves on slab waveguide steps: effects of rounded edges - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
Oblique propagation of semi-guided waves across slab waveguide structures with bent corners is investigated. A critical angle can be defined beyond which all radiation losses are suppressed. Additionally an increase of the curvature radius of the bends also leads to low-loss configurations for incidence angles below that critical angle. A combination of two bent corner systems represents a step-like structure, behaving like a Fabry-Perot interferometer, with two partial reflectors separated by the vertical height between the horizontal slabs. We numerically analyse typical high-index-contrast Si/SiO2 structures for their reflectance and transmittance properties. When increasing the curvature radius the resonant effect becomes less relevant such that full transmittance is reached with less critical conditions on the vertical distance or the incidence angle. For practical interest 3-D problems are considered, where the structures are excited by the fundamental mode of a wide, shallow rib waveguide. High transmittance levels can be observed also for these 3-D configurations depending on the width of the rib.
Keywords: tet_topic_waveguide

Oblique Semi-Guided Waves: 2-D Integrated Photonics with Negative Effective Permittivity - Hammer, Manfred; Ebers, Lena; Hildebrandt, Andre; Alhaddad, Samer; Förstner, Jens (2018 IEEE 17th International Conference on Mathematical Methods in Electromagnetic Theory (MMET))
Semi-guided waves confined in dielectric slab waveguides are being considered for oblique angles of propagation. If the waves encounter a linear discontinuity of (mostly) arbitrary shape and extension, a variant of Snell's law applies, separately for each pair of incoming and outgoing modes. Depending on the effective indices involved, and on the angle of incidence, power transfer to specific outgoing waves can be allowed or forbidden. In particular, critical angles of incidence can be identified, beyond which any power transfer to non-guided waves is forbidden, i.e. all radiative losses are suppressed. In that case the input power is carried away from the discontinuity exclusively by reflected semi-guided waves in the input slab, or by semi-guided waves that are transmitted into other outgoing slab waveguides. Vectorial equations on a 2-D cross sectional domain apply. These are formally identical to the equations that govern the eigenmodes of 3-D channel waveguides. Here, however, these need to be solved not as an eigenvalue problem, but as an inhomogeneous problem with a right-hand-side that is given by the incoming semi-guided wave, and subject to transparent boundary conditions. The equations resemble a standard 2-D Helmholtz problem, with an effective permittivity in place of the actual relative permittivity. Depending on the properties of the incoming wave, including the angle of incidence, this effective permittivity can become locally negative, causing the suppression of propagating outgoing waves. A series of high-contrast example configurations are discussed, where these effects lead to - in some respects - quite surprising transmission characteristics.
Keywords: tet_topic_waveguides

Application of the Discontinuous Galerkin Time Domain Method in Nonlinear Nanoplasmonics - Grynko, Yevgen; Förstner, Jens (2018 IEEE 17th International Conference on Mathematical Methods in Electromagnetic Theory (MMET))
Keywords: tet_topic_numerics; tet_topic_shg

Polarization Conversion Effect in Biological and Synthetic Photonic Diamond Structures - Wu, Xia; Rodríguez-Gallegos, Fernando L.; Heep, Marie-Christin; Schwind, Bertram; Li, Guixin; Fabritius, Helge-Otto; von Freymann, Georg; Förstner, Jens (Advanced Optical Materials)
Polarization of light is essential for some living organisms and many optical applications. Here, an orientation dependent polarization conversion effect is reported for light reflected from diamond‐structure‐based photonic crystals (D‐structure) inside the scales of a beetle, the weevil Entimus imperialis. When linearly polarized light propagates along its 〈100〉 directions, the D‐structure behaves analogous to a half‐wave plate in reflection but based on a different mechanism. The D‐structure rotates the polarization direction of linearly polarized light, and reflects circularly polarized light of both handednesses without changing it. This polarization effect is different from circular dichroism occurring in chiral biological photonic structures discovered before. The structural origin of this effect is symmetry breaking inside D‐structure's unit cell. This finding demonstrates that natural photonic structures can exploit multiple functionalities inherent to the design principles of their structural organization. Aiming at transferring the inherent polarization effect of the biological D‐structure to technically realizable materials, three simplified biomimetic structural models are derived and it is theoretically demonstrated that they retain the effect. Out of these structures, functioning woodpile structure prototypes are fabricated.
Keywords: tet_topic_phc; tet_topic_bio

Unveiling and Imaging Degenerate States in Plasmonic Nanoparticles with Nanometer Resolution - Myroshnychenko, Viktor; Nishio, Natsuki; García de Abajo, F. Javier; Förstner, Jens; Yamamoto, Naoki (ACS Nano)
Metal nanoparticles host localized plasmon excitations that allow the manipulation of optical fields at the nanoscale. Despite the availability of several techniques for imaging plasmons, direct access into the symmetries of these excitations remains elusive, thus hindering progress in the development of applications. Here, we present a combination of angle-, polarization-, and space-resolved cathodoluminescence spectroscopy methods to selectively access the symmetry and degeneracy of plasmonic states in lithographically fabricated gold nanoprisms. We experimentally reveal and spatially map degenerate states of multipole plasmon modes with nanometer spatial resolution and further provide recipes for resolving optically dark and out-of-plane modes. Full-wave simulations in conjunction with a simple tight-binding model explain the complex plasmon structure in these particles and reveal intriguing mode-symmetry phenomena. Our approach introduces systematics for a comprehensive symmetry characterization of plasmonic states in high-symmetry nanostructures.
Keywords: tet_topic_plasmonics

Intensity surge and negative polarization of light from compact irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We study the dependence of the intensity and linear polarization of light scattered by isolated particles with the compact irregular shape on their size using the discontinuous Galerkin time domain numerical method. The size parameter of particles varies in the range of X = 10 to 150, and the complex refractive index is m = 1.5 + 0i. Our results show that the backscattering negative polarization branch weakens monotonously, but does not disappear at large sizes, up to the geometrical optics regime, and can be simulated without accounting for wave effects. The intensity backscattering surge becomes narrower with increasing particle size. For X = 150, the surge width is several degrees.
Keywords: tet_topic_scattering

Simulation leitungsgeführter Störspannungen von DC-DC-Wandlern - Baumgarten, Tim; Scholz, Peter; Sievers, Denis; Förstner, Jens (Elektromagnetische Verträglichkeit - Internationale Fachmesse und Kongress 2018)
In diesem Beitrag werden simulatorische und messtechnische EMV-Untersuchungen von Gleichspannungswandlern vorgestellt. Der Fokus liegt auf leitungsgeführten Störspannungen, ihre Abhängigkeit vom Schaltungslayout und ihre Unterdrückung durch Filterung. Der Simulationsprozess besteht aus kombinierten Feld- und Netzwerksimulationen. Zur Bewertung der Simulationsresultate werden zwei Prototypen gezeigt, die gute und schlechte EMV-Eigenschaften aufweisen. Bei der Beurteilung der Resultate wird insbesondere Wert auf die Untersuchung gelegt, inwieweit einfache Schaltungssimulationen ausreichen, um leitungsgeführte Störspannungen korrekt vorherzusagen und wann aufwändigere Feldsimulationen notwendig sind.

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

OpenCL-based FPGA Design to Accelerate the Nodal Discontinuous Galerkin Method for Unstructured Meshes - Kenter, Tobias; Mahale, Gopinath; Alhaddad, Samer; Grynko, Yevgen; Schmitt, Christian; Afzal, Ayesha; Hannig, Frank; Förstner, Jens; Plessl, Christian (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
The exploration of FPGAs as accelerators for scientific simulations has so far mostly been focused on small kernels of methods working on regular data structures, for example in the form of stencil computations for finite difference methods. In computational sciences, often more advanced methods are employed that promise better stability, convergence, locality and scaling. Unstructured meshes are shown to be more effective and more accurate, compared to regular grids, in representing computation domains of various shapes. Using unstructured meshes, the discontinuous Galerkin method preserves the ability to perform explicit local update operations for simulations in the time domain. In this work, we investigate FPGAs as target platform for an implementation of the nodal discontinuous Galerkin method to find time-domain solutions of Maxwell's equations in an unstructured mesh. When maximizing data reuse and fitting constant coefficients into suitably partitioned on-chip memory, high computational intensity allows us to implement and feed wide data paths with hundreds of floating point operators. By decoupling off-chip memory accesses from the computations, high memory bandwidth can be sustained, even for the irregular access pattern required by parts of the application. Using the Intel/Altera OpenCL SDK for FPGAs, we present different implementation variants for different polynomial orders of the method. In different phases of the algorithm, either computational or bandwidth limits of the Arria 10 platform are almost reached, thus outperforming a highly multithreaded CPU implementation by around 2x.
Keywords: tet_topic_hpc

Radar backscattering from a large-grain cometary coma: numerical simulation - Dogra, Shraddha; Grynko, Yevgen; Zubko, Evgenij; Förstner, Jens (Astronomy & Astrophysics)
We numerically simulate the circular polarization ratio of the radar signal backscattered from a large-grain cometary coma and compare the simulation results with the radar measurements for seven comets. We apply the discrete dipole approximation method and a model of random irregular particles. Our results confirm water ice composition of the cm-sized chunks detected by the NASA Deep Impact space probe in the vicinity of the nucleus of Comet 103P/Hartley 2. The index of the power-law size distribution in this case can be constrained to the range n ≈ 3.3–4.3. For the other considered comets the circular polarization ratio can be reproduced with variations of the power index between 2 and 5.
Keywords: tet_topic_scattering

Guided Wave Interaction in Photonic Integrated Circuits — A Hybrid Analytical/Numerical Approach to Coupled Mode Theory - Hammer, Manfred (Recent Trends in Computational Photonics)
Frequently, optical integrated circuits combine elements (waveguide channels, cavities), the simulation of which is well established through mature numerical eigenproblem solvers. It remains to predict the interaction of these modes. We address this task by a general, “Hybrid” variant (HCMT) of Coupled Mode Theory. Using methods from finite-element numerics, the properties of a circuit are approximated by superpositions of eigen-solutions for its constituents, leading to quantitative, computationally cheap, and easily interpretable models.
Keywords: tet_topic_waveguide; tet_topic_numerics

Hybrid coupled-mode modeling in 3D: perturbed and coupled channels, and waveguide crossings - Hammer, Manfred; Alhaddad, Samer; Förstner, Jens (Journal of the Optical Society of America B)
The 3D implementation of a hybrid analytical/numerical variant of the coupled-mode theory is discussed. Eigenmodes of the constituting dielectric channels are computed numerically. The frequency-domain coupled-mode models then combine these into fully vectorial approximations for the optical electromagnetic fields of the composite structure. Following a discretization of amplitude functions by 1D finite elements, pro- cedures from the realm of finite-element numerics are applied to establish systems of linear equations for the then- discrete modal amplitudes. Examples substantiate the functioning of the technique and allow for some numerical assessment. The full 3D simulations are highly efficient in memory consumption, moderately demanding in com- putational time, and, in regimes of low radiative losses, sufficiently accurate for practical design. Our results include the perturbation of guided modes by changes of the refractive indices, the interaction of waves in parallel, horizontally or vertically coupled straight waveguides, and a series of crossings of potentially overlapping channels with fairly arbitrary relative positions and orientations.
Keywords: tet_topic_waveguide; tet_topic_numerics

Spiral modes supported by circular dielectric tubes and tube segments - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optical and Quantum Electronics)
The modal properties of curved dielectric slab waveguides are investigated. We consider quasi-confined, attenuated modes that propagate at oblique angles with respect to the axis through the center of curvature. Our analytical model describes the transition from scalar 2-D TE/TM bend modes to lossless spiral waves at near-axis propagation angles, with a continuum of vectorial attenuated spiral modes in between. Modal solutions are characterized in terms of directional wavenumbers and attenuation constants. Examples for vectorial mode profiles illustrate the effects of oblique wave propagation along the curved slab segments. For the regime of lossless spiral waves, the relation with the guided modes of corresponding dielectric tubes is demonstrated.
Keywords: tet_topic_waveguide

Direction-tunable enhanced emission from a subwavelength metallic double-nanoslit structure - Song, Xiaohong; Wang, Nini; Yan, Ming; Lin, Cheng; Förstner, Jens; Yang, Weifeng (Optics Express)
Controlling light emission out of subwavelength nanoslit/aperture structures is of great important for highly integrated photonic circuits. Here we propose a new method to achieve direction-tunable emission based on a compact metallic microcavity with double nanoslit. Our method combines the principles of Young’s interference and surface plasmon polaritons interference. We show that the direction of the far-field beam can be controlled over a wide range of angles by manipulating the frequency and relative phase of light arriving at the two slits, which holds promise for applications in the ultracompact optoelectronic devices.
Keywords: tet_topic_plasmonics

Simulation of Second Harmonic Generation from Photonic Nanostructures Using the Discontinuous Galerkin Time Domain Method - Grynko, Yevgen; Förstner, Jens (Recent Trends in Computational Photonics)
We apply the Discontinuous Galerkin Time Domain (DGTD) method for numerical simulations of the second harmonic generation from various metallic nanostructures. A Maxwell–Vlasov hydrodynamic model is used to describe the nonlinear effects in the motion of the excited free electrons in a metal. The results are compared with the corresponding experimental measurements for split-ring resonators and plasmonic gap antennas.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Flexible FPGA design for FDTD using OpenCL - Kenter, Tobias; Förstner, Jens; Plessl, Christian (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Compared to classical HDL designs, generating FPGA with high-level synthesis from an OpenCL specification promises easier exploration of different design alternatives and, through ready-to-use infrastructure and common abstractions for host and memory interfaces, easier portability between different FPGA families. In this work, we evaluate the extent of this promise. To this end, we present a parameterized FDTD implementation for photonic microcavity simulations. Our design can trade-off different forms of parallelism and works for two independent OpenCL-based FPGA design flows. Hence, we can target FPGAs from different vendors and different FPGA families. We describe how we used pre-processor macros to achieve this flexibility and to work around different shortcomings of the current tools. Choosing the right design configurations, we are able to present two extremely competitive solutions for very different FPGA targets, reaching up to 172 GFLOPS sustained performance. With the portability and flexibility demonstrated, code developers not only avoid vendor lock-in, but can even make best use of real trade-offs between different architectures.
Keywords: tet_topic_hpc

Second harmonic generation spectroscopy on hybrid plasmonic/dielectric nanoantennas - Linnenbank, Heiko; Grynko, Yevgen; Förstner, Jens; Linden, Stefan (Light: Science & Applications)
Keywords: tet_topic_opticalantenna; tet_topic_shg

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Light scattering by ice crystals of cirrus clouds: From exact numerical methods to physical-optics approximation - Konoshonkin, Alexander; Borovoi, Anatoli; Kustova, Natalia; Okamoto, Hajime; Ishimoto, Hiroshi; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The problem of light scattering by ice crystals of cirrus clouds is considered in the case of a hexagonal ice plate with different distributions over crystal orientations. The physical-optics approximation based on (E, M)-diffraction theory is compared with two exact numerical methods: the finite difference time domain (FDTD) and the discontinuous Galerkin time domain (DGTD) in order to estimate its accuracy and limits of applicability. It is shown that the accuracy of the physical-optics approximation is estimated as 95% for the averaged backscattering Mueller matrix for particles with size parameter more than 120. Furthermore, the simple expression that allows one to estimate the minimal number of particle orientations required for appropriate spatial averaging has been derived.
Keywords: tet_topic_scattering

Comparison between the physical-optics approximation and exact methods solving the problem of light scattering by ice crystals of cirrus clouds - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Okamoto, H.; Sato, K.; Ishimoto, H.; Grynko, Yevgen; Förstner, Jens (22nd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics)
In the problem of light scattering by ice crystals of cirrus clouds, two exact methods (FDTD – finite difference time domain and DGTD – discontinuous Galerkin time domain) and the physical-optics approximation are used for numerical calculations of the Mueller matrix in the case of ice hexagonal plates and columns. It is shown that for the crystals larger than 10 μm at the wavelength of 0.532 μm the exact methods and physical-optics approximation closely agreed within three diffraction fringes about the centers of the diffraction patterns. As a result, in the case of random orientation of these crystals, the physical-optics approximation provides accuracy 95% for the averaged Mueller matrix.
Keywords: tet_topic_scattering

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Light scattering by irregular particles much larger than the wavelength with wavelength-scale surface roughness - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We simulate light scattering by random irregular particles that have dimensions much larger than the wavelength of incident light at the size parameter of 𝑋=200 using the discontinuous Galerkin time domain method. A comparison of the DGTD solution for smoothly faceted particles with that obtained with a geometric optics model shows good agreement for the scattering angle curves of intensity and polarization. If a wavelength-scale surface roughness is introduced, diffuse scattering at rough interface results in smooth and featureless curves for all scattering matrix elements which is consistent with the laboratory measurements of real samples.
Keywords: tet_topic_scattering

Light scattering by ice crystals of cirrus clouds: comparison of the physical optics methods - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The physical optics approximations are derived from the Maxwell equations. The scattered field equations by Kirchhoff, Stratton-Chu, Kottler and Franz are compared and discussed. It is shown that in the case of faceted particles, these equations reduce to a sum of the diffraction integrals, where every diffraction integral is associated with one plane–parallel optical beam leaving a particle facet. In the far zone, these diffraction integrals correspond to the Fraunhofer diffraction patterns. The paper discusses the E-, M- and (E, M)-diffraction theories as applied to ice crystals of cirrus clouds. The comparison to the exact solution obtained by the discontinuous Galerkin time domain method shows that the Kirchhoff diffraction theory is preferable.
Keywords: tet_topic_scattering

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

Wave interaction in photonic integrated circuits: Hybrid analytical / numerical coupled mode modeling - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XX)
Typical optical integrated circuits combine elements, like straight and curved waveguides, or cavities, the simulation and design of which is well established through numerical eigenproblem-solvers. It remains to predict the interaction of these modes. We address this task by a ”Hybrid” variant (HCMT) of Coupled Mode Theory. Using methods from finite-element numerics, the optical properties of a circuit are approximated by superpositions of eigen-solutions for its constituents, leading to quantitative, low-dimensional, and interpretable models in the frequency domain. Spectral scans are complemented by the direct computation of supermode properties (spectral positions and linewidths, coupling-induced phase shifts). This contribution outlines the theoretical background, and discusses briefly limitations and implementational details, with the help of an example of a 2-D coupled-resonator-optical-waveguide configuration.
Keywords: tet_topic_waveguide; tet_topic_numerics

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Planar prism spectrometer based on adiabatically connected waveguiding slabs - Civitci, F.; Hammer, Manfred; Hoekstra, H.J.W.M. (Optics Communications)
The device principle of a prism-based on-chip spectrometer for TE polarization is introduced. The spectrometer exploits the modal dispersion in planar waveguides in a layout with slab regions having two different thicknesses of the guiding layer. The set-up uses parabolic mirrors, for the collimation of light of the input waveguide and focusing of the light to the receiver waveguides, which relies on total internal reflection at the interface between two such regions. These regions are connected adiabatically to prevent unwanted mode conversion and loss at the edges of the prism. The structure can be fabricated with two wet etching steps. The paper presents basic theory and a general approach for device optimization. The latter is illustrated with a numerical example assuming SiON technology.
Keywords: tet_topic_waveguide

Full Resonant Transmission of Semiguided Planar Waves Through Slab Waveguide Steps at Oblique Incidence - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Journal of Lightwave Technology)
Sheets of slab waveguides with sharp corners are investigated. By means of rigorous numerical experiments, we look at oblique incidence of semi-guided plane waves. Radiation losses vanish beyond a certain critical angle of incidence. One can thus realize lossless propagation through 90-degree corner configurations, where the remaining guided waves are still subject to pronounced reflection and polarization conversion. A system of two corners can be viewed as a structure akin to a Fabry-Perot-interferometer. By adjusting the distance between the two partial reflectors, here the 90-degree corners, one identifies step-like configurations that transmit the semi-guided plane waves without radiation losses, and virtually without reflections. Simulations of semi-guided beams with in-plane wide Gaussian profiles show that the effect survives in a true 3-D framework.
Keywords: tet_topic_waveguide

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

A process for the preparation of a population inversion in a quantum system using multi-pulse excitation - Zrenner, Artur; Förstner, Jens; Mantei, Dirk
Die Erfindung betrifft ein Verfahren zur Präparation einer Besetzungsinversion in einem Quantensystem (Q) mittels Mehrpulsanregung, wobei ein Quantensystem (Q) umfassend wenigstens einen Quantenpunkt mit zwei orthogonalen Zuständen (/X>, /Y>), insbesondere die mit zueinander orthogonalen Polarisationen (P1, P2) optisch anregbar sind, mit einem ersten Laserpuls (L1) beleuchtet wird, welcher zur resonanten Anregung des ersten (/Y>) der zwei Zustände (/X>, /Y>) eingestellt wird und zeitlich nachfolgend mit einem zweiten Laserpuls (L2) beleuchtet wird, der zur resonanten Anregung des zweiten (/X>) der zwei Zustände (/X>, /Y>) eingestellt wird.
Keywords: tet_topic_qd

Oblique incidence of semi-guided waves on rectangular slab waveguide discontinuities: A vectorial QUEP solver - Hammer, Manfred (Optics Communications)
The incidenceofthin-film-guided, in-planeunguidedwavesatobliqueanglesonstraightdiscontinuities of dielectricslabwaveguides,anearlyproblemofintegratedoptics,isbeingre-considered.The3-D frequencydomainMaxwellequationsreducetoaparametrizedinhomogeneousvectorialproblemona 2-D computationaldomain,withtransparent-influx boundaryconditions.Weproposearigorousvec- torial solverbasedonsimultaneousexpansionsintopolarizedlocalslabeigenmodesalongthetwo orthogonal crosssectioncoordinates(quadridirectionaleigenmodepropagationQUEP).Thequasi-ana- lytical schemeisapplicabletoconfigurations with — in principle — arbitrary crosssectiongeometries. Examples forahigh-contrastfacetofanasymmetricslabwaveguide,forthelateralexcitationofa channel waveguide,andforastepdiscontinuitybetweenslabwaveguidesofdifferentthicknessesare discussed.
Keywords: tet_topic_waveguide; tet_topic_numerics

General relation for group delay and the relevance of group delay for refractometric sensing - Hoekstra, Hugo J. W. M.; Hammer, Manfred (Journal of the Optical Society of America B)
The relevance of our definition for sensitivity in refractometric sensing, being the relative change in the transmittance of a certain output channel of an optical device over the change in the refractive index of the probed material, is discussed. It is compared to one based on spectral shift per refractive index unit change. Further, there is discussion on how group delay and sensitivity are interrelated and can be converted into each other and which physical quantities are relevant for high sensitivity. As a by-product of the theory presented, a general expression relating group delay and the ratio of the time-averaged optical energy and the input power is presented.
Keywords: tet_topic_waveguide

Light Scattering By Random Irregular Particles With Different Morphology - Grynko, Yevgen; Zubko, Evgenij
We simulate numerically light scattering by random irregular particles of two classes of shape: Gaussian random field particles and agglomerated debri particles. Comparison of the angular dependencies of the scattering matrix elements for the case of non-absorbing material shows qualitative similarity of optical properties of both types despite different morphology of scatterers. Absorbing particles result in the difference in linear polarization. However, a strong similarty remains for the intensity curves.

Engineering plasmonic and dielectric directional nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVIII)
Optical and infrared antennas provide a promising way to couple photons in and out of nanoscale structures. As counterpart to conventional radio antennas, they are able to increase optical felds in sub-wavelength volumes, to enhance excitation and emission of quantum emitters or to direct light, radiated by quantum emitters. The directed emission of these antennas has been mainly pursued by surface plasmon based devices, e.g. Yagi-Uda like antennas, which are rather complicated due to the coupling of several metallic particles. Also, like all metallic structures in optical or infrared regime, these devices are very sensitive to fabrication tolerances and are affected by strong losses. It has been shown recently, that such directed emission can be accomplished by dielectric materials as well. In this paper we present an optimization of nanoscopic antennas in the near infrared regime starting from a metallic Yagi-Uda structure. The optimization is done via a particle-swarm algorithm, using full time domain finite integration simulations to obtain the characteristics of the investigated structure, also taking into account substrates. Furthermore we present a dielectric antenna, which performs even better, due to the lack of losses by an appropriate choice of the dielectric material. These antennas are robust concerning fabrication tolerances and can be realized with different materials for both the antenna and the substrate, without using high index materials.
Keywords: tet_topic_opticalantenna

Accelerating Finite Difference Time Domain Simulations with Reconfigurable Dataflow Computers - Giefers, Heiner; Plessl, Christian; Förstner, Jens (ACM SIGARCH Computer Architecture News)
Keywords: funding-maxup; tet_topic_hpc

Light scattering by randomly irregular dielectric particles larger than the wavelength - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optical Letters)
Keywords: tet_topic_scattering

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta

Optimal second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVII)
Previous experimental measurements and numerical simulations give evidence of strong electric and magnetic field interaction between split-ring resonators in dense arrays. One can expect that such interactions have an influence on the second harmonic generation. We apply the Discontinuous Galerkin Time Domain method and the hydrodynamic Maxwell-Vlasov model to simulate the linear and nonlinear optical response from SRR arrays. The simulations show that dense placement of the constituent building blocks appears not always optimal and collective effects can lead to a significant suppression of the near fields at the fundamental frequency and, consequently, to the decrease of the SHG intensity. We demonstrate also the great role of the symmetry degree of the array layout which results in the variation of the SHG efficiency in range of two orders of magnitude.
Keywords: tet_topic_shg; tet_topic_meta

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Enhanced FDTD edge correction for nonlinear effects calculation - Classen, C; Förstner, Jens; Meier, Torsten; Schuhmann, R (2010 IEEE Antennas and Propagation Society International Symposium)
The electromagnetic field in the vicinity of sharp edges needs a special treatment in numeric calculation whenever accurate, fast converging results are necessary. One of the fundamental works concerning field singularities has been proposed in 1972 [1] and states that the electromagnetic energy density must be integrable over any finite domain, even if this domain contains singularities. It is shown, that the magnetic field H(, ϕ) and electric field E(, ϕ) are proportional to ∝ (t−1) for → 0. The variable is the distance to the edge and t has to fulfill the integrability condition and thus is restricted to 0 < t < 1. This result is often used to reduce the error corresponding to the singularity without increasing the numerical effort [2 - 5]. For this purpose, a correction factor K is estimated by inserting the proportionality into the wave equation. It is shown, that this method improves the accuracy of the result significantly, however the order of convergence is often not studied. In [4] a method to modify the material parameters in order to use analytic results to improve the numeric calculation is presented. In this contribution we will - inspired by the scheme given in [4] - develop a new method to estimate a correction factor for perfect conducting materials (PEC) and demonstrate the improvement of the results compared to the standard edge correction. Therefore analytic results (comparable to [1]) are consequently merged with the scheme in [4]. The main goal of this work is the calculation of the second harmonic generation (SHG) in the wave response of so-called metamaterials [6]. Frequently these structures contain sharp metallic edges with field singularities at the interfaces which have a strong impact on the SHG signals. Thus, an accurate simulation of singularities is highly important. However, the following approach can also be applied to many other setups, and one of them is shown in the example below.
Keywords: tet_topic_numerics